2019
DOI: 10.22456/1982-8918.88631
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação De Desempenho Do Programa Academia Da Saúde Em Belo Horizonte: Um Estudo De Caso

Abstract: Esta pesquisa realizou uma avaliação de desempenho em um polo do Programa Academia da Saúde em Belo Horizonte/MG. É uma pesquisa qualitativa, descritiva, do tipo estudo de caso. A escolha do polo e dos participantes foi intencional. Adotamos a entrevista em profundidade para a coleta dos dados, sendo que a amostra foi estipulada pela técnica de saturação. Para a interpretação das informações usamos a análise crítica do discurso. Os resultados indicam algumas lacunas existentes no programa, como aspectos logíst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
28
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(32 citation statements)
references
References 5 publications
2
28
0
2
Order By: Relevance
“…Also, the present study reports additional health benefits than reported by previous studies 8,12,29 , relating to the improvement of cognitive, communicative and emotional skills among ASP´s users. Then, the findings showed that the impact of ASP unit´s activities on users´ lives was broader than physical effects, such as physical fitness and pain relief.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…Also, the present study reports additional health benefits than reported by previous studies 8,12,29 , relating to the improvement of cognitive, communicative and emotional skills among ASP´s users. Then, the findings showed that the impact of ASP unit´s activities on users´ lives was broader than physical effects, such as physical fitness and pain relief.…”
Section: Discussionsupporting
confidence: 58%
“…It is already known that Health and Physical Education professionals (HPEP) prevail as workforce in the ASP and the activities that are often conducted involve group interventions directed at regular physical activity and healthy eating habits 3,[6][7] . Studies [8][9][10][11] have also demonstrated that the majority of ASP´s users are middle-age and older women, who showed high levels of satisfaction with the programme and perceptions of increased quality of life, pleasure and social interaction as resulting from their participation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…O PAS se destaca como um programa que visa qualificar as ações de promoção da saúde. Preconiza-se que, as atividades desenvolvidas em seu âmbito sejam culturalmente inseridas e adaptadas aos territórios, sendo um potencial elemento para o aumento dos níveis de AF na população (MACIEL et al, 2019;MALTA et al, 2014;BRASIL, 2013). De acordo com o sistema de monitoramento do PAS, em 2017, o número de polos habilitados era de 4.271 em todas as regiões brasileiras e suas atividades alcançaram mais de 2.500 municípios, com potencial para cobrir um milhão de pessoas (FLORINDO et al, 2016).…”
Section: Introductionunclassified
“…Observa-se que a QV apresenta uma relação direta e positiva com a AF e a AS. Ao considerar que ambas podem ser fatores de proteção de doenças crônicas, elas se tornam importantes para a manutenção de hábitos saudáveis (MACIEL et al, 2019;MEIRELES;FERREIRA, 2018;DIETTRICH;PEDRO, 2015;CAMPOS et al, 2014). Ademais, níveis satisfatórios de AF e AS são descritos em outros estudos como um diferencial na percepção da QV, especialmente por contribuir diretamente na capacidade funcional, aspectos físicos, dor e saúde geral (FEITOSA et al, 2016;DIETTRICH;PEDRO, 2015;GONÇALVES et al, 2019).…”
unclassified